Preclinical Evidence for the Interplay between Oxidative Stress and RIP1-Dependent Cell Death in Neurodegeneration: State of the Art and Possible Therapeutic Implications - Danuta Jantas; Władysław Lasoń (MDPI AG, 2021)
Neurodegenerative diseases are the most frequent chronic, age-associated neurological pathologies having a major impact on the patient's quality of life. Despite a heavy medical, social and economic burden they pose, no causative treatment is available for these diseases. Among the important pathogenic factors contributing to neuronal loss during neurodegeneration is elevated oxidative stress resulting from a disturbed balance between endogenous prooxidant and antioxidant systems. For many years, it was thought that increased oxidative stress was a cause of neuronal cell death executed via an apoptotic mechanism. However, in recent years it has been postulated that rather programmed necrosis (necroptosis) is the key form of neuronal death in the course of neurodegenerative diseases. Such assumption was supported by biochemical and morphological features of the dying cells as well as by the fact that various necroptosis inhibitors were neuroprotective in cellular and animal models of neurodegenerative diseases. In this review, we discuss the relationship between oxidative stress and RIP1-dependent necroptosis and apoptosis in the context of the pathomechanism of neurodegenerative disorders. Based on the published data mainly from cellular models of neurodegeneration linking oxidative stress and necroptosis, we postulate that administration of multipotential neuroprotectants with antioxidant and antinecroptotic properties may constitute an efficient pharmacotherapeutic strategy for the treatment of neurodegenerative diseases.